Transforming Conflict Response with IoT: Innovations, Challenges, and Ethical Considerations in Humanitarian Aid Delivery - Parmadia, Budi Dhaju; Ramlib, Kallamullah (Devotion : Journal of Research and Community Service, 2025)
The integration of Internet of Things (IoT) technologies in humanitarian aid holds transformative potential for conflict zones but faces critical challenges, including infrastructure degradation, cybersecurity risks, and ethical dilemmas. This study systematically reviews 75 peer-reviewed sources (2019–2024) using the PRISMA methodology to analyze IoT adoption barriers and innovations. Findings reveal that decentralized architectures (e.g., blockchain, mesh networks) and AI-driven security (e.g., intrusion detection) can mitigate infrastructure and cyber vulnerabilities, while participatory design and ethical frameworks address techno-colonialism and data sovereignty concerns. The research contributes actionable recommendations for scalable, culturally sensitive IoT deployments, emphasizing hybrid connectivity (LoRa, satellite) and sustainable practices (biodegradable sensors). Implications include fostering multi-stakeholder collaboration, standardized protocols, and longitudinal field testing to ensure resilience and equity in humanitarian operations. This study bridges theoretical and practical gaps, offering a holistic roadmap for ethically grounded IoT solutions in high-risk environments.